Ethnic profiling of organised crime? A tendency of mafia-cation in the Netherlands - Eski, Yarin (Trends in organized crime, 2024)
This article will explore how the current narratives (and corresponding changes) in Dutch organised crime policing relate to ethnic profiling of minorities in the Netherlands. It will do so by developing a theoretically informed narrative understanding of what we would like to conceptualise as ethnic profiling of organised crime (in the Netherlands), digging deeper into the connection between the role of ethnicity in organised crime studies inasmuch as it relates to the history of the mafia concept and, even further, lingering colonialism in law-and-order approaches. By focusing on (assumed) socio-historical connections between Italy, mafia and organised crime and on the social construction of Italian mafia as organised crime, based on narrative criminology, this article discursively and interpretatively understands the dominant and hidden Dutch narratives on (policing) organised crime. The discovered narratives will be critically discussed in light of the juxtaposition between mafias and ethnic organised crime and post-colonial implications.